Antecedents and Impacts of Green Process Innovation on Performance: A Study on Jamu MSMEs - Hunik Sri Runing Sawitri; Asri Laksmi Riani; Salamah Wahyuni; Suryandari Istiqomah; Ariyani Wahyu Wijayanti (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
This study seeks to examine the influence of CEO education on the correlation between managerial competence and ESG. This study employs a sample of 185 observations from 37 manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. This study used the weighted least squares regression model for estimation purposes. The research findings indicate that managerial skill impacts ESG, aligning with legitimacy theory. The theory suggests that superior managerial capability facilitates an understanding of stakeholder demands through ESG disclosures, thereby enhancing a company’s reputation and legitimacy. Nevertheless, the outcomes indicate that CEO education as a moderating element does not enhance the impact of managerial competence on ESG. A manager’s education does not influence ESG disclosure. The limited sample of manufacturing enterprises that issue ESG disclosure reports and the temporal scope, spanning only five years, constrain the research.